Deported Men's and Father's Perspective: The Impacts of Family Separation on Children and Families in the U.S. - Ojeda, Victoria D.; Magana, Christopher; Burgos, Jose Luis; Vargas-Ojeda, Adriana Carolina (Frontiers in Psychiatry, 2020)
Background: Family separation due to the deportation of a migrant is pervasive, yet less is known about its potential impacts on the social, economic and mental well-being of families remaining in the United States. Methods: We conducted a mixed-methods study. In 2013, 303 Mexican male nationals completed an interviewer-administered questionnaire at a free clinic in Tijuana, Mexico. For this analysis, participants were: (1) ≥18 years; (2) seeking services; (3) Spanish or English speakers and (4) reported a U.S. deportation. Participants answered migration history items and open-ended questions regarding the impact of their deportation on U.S.-based family members. We present descriptive statistics and illustrative quotes for themes identified in the qualitative text data. Using a grounded-theory approach, we considered all data to develop a conceptual framework that others may use to study the consequences of family separation due to deportation. Results: Nearly two-thirds of participants reported living in the U.S. for 11+ years, a similar proportion reported 2+ deportations, and 31% reported being banned from re-entering the U.S. for 11+ years. More than one-half of participants were separated from their nuclear families (spouse/partner and/or children). Deportees who were separated from any family members reported that their families lost income for basic needs (rent/utilities: 50%, food: 44%, clothing: 39%, daycare: 16%, health insurance:15%); school participation was also negatively impacted (31%). Qualitative data revealed that children <=18 years remaining in the U.S. experienced mental health symptoms post-parental deportation (i.e., persistent crying, depression, sadness, anger, resentment). Deported fathers consistently expressed frustration at being unable to provide love, care, support, mentorship for their children. Based on our mixed-methods approach, we propose a framework to systematically study the consequences of family separation due to the deportation of fathers. Conclusion: Findings are consistent with the extant research. Binational interventions to support families that experience forced-separation are needed to mitigate short and long-term adverse mental health outcomes, especially among youth in the U.S., and other unfavorable family and household-level outcomes. Funding to understand the implications of maternal deportation and for longitudinal qualitative and quantitative research on migrant-focused interventions and related outcomes is needed.